Inventive problem-solving in project-based learning on design and technology: a needs analysis for module development / Tee Tze Kiong ... [et al.] - Tee, Tze Kiong; Mohd Rusly, Noor Syuhaili; Abd Hamid, Ruhiana Idayu; Swaran Singh, Charanjit Kaur; Hanapi, Zaliza (Universiti Teknologi MARA, 2022)
Education in Malaysia is transforming to increase students’ ability and meet the needs of the industry. In Design and Technology subject, students apply the technology to develop a product capable of solving problems through a project-based learning approach. Therefore, this study aims to (a) identify problems in the implementation of design project and (b) identify the needs for module development. An online survey was conducted on 140 Design and Technology subject teachers in Batu Pahat district, Johor. Findings showed that the overall level of problem in the implementation of project-based learning was high and there was no significant difference in perception of problems in implementing projectbased learning by gender, but a significant difference of perception by teaching experience. In terms of module content, the overall findings showed that the content requirement in the module was high. Gender and teaching experience showed no significant difference in perception of module content requirement. Finally, the findings showed that the suggested module design features are using Arial font and multi-colour, content in point form, A4 size, and contain graphical content. Therefore, it is proposed that this module should be developed due to its high requirements and should meet the needs of users, so that the goals of project implementation can be achieved.